The effectiveness of educational scaffolding strategy in chemical problem solving skills and motivation for achievement in the fourth grade students. - A., P. Hiam Ghaieb Hussein (International Journal of Psychosocial Rehabilitation, 2020)
This research aims to know the effectiveness of the educational scaffolding strategy on the skills of solving the chemical problems and motivation issues of the achievement among the fourth-grade scientists. The results of the study were divided into two equal groups, one experimental and the other control. The research tools test the skills of solving the chemical problems of the multi-test type and the questionnaire. To measure the motivation for achievement in the students and after the statistical treatment the results of the study, there were statically significant differences between the experimental group and the control group In the testing of chemical problem-solving skills and the motivation scale for achievement and for the benefit of the experimental group, In light of the results. The study recommended the use of the strategy of educational scaffolding as one of the effective strategies to gain the skills of solving chemical problems and motivation of achievement among students and to guide the preparation of chemistry curricula by incorporating skills in solving chemical problems in the curriculum.